Mapping of Early Childhood Education’s Capacity in the Implementation of Inclusive Education in Malang City - Erfantinni, Imroatul Hayyu; Anisa Farah Nurmila Rizke; Izzatul Firdaus; Indi Diana Fakhriya (CV. Media Digital Publikasi Indonesia, 2025)
The capacity to implement Early Childhood Education serves as a key quality benchmark in inclusive education, facilitating education for children with special needs alongside regular students. With increasing demand for inclusive schools, it is crucial to map educational institutions' capacities. This research aims to assess the capacity for inclusive education implementation in Malang City. According to the Ministry of Education and Culture, inclusive education capacity covers 14 aspects: regulations, management, funding, organization, socialization, physical environment, facilities, services, human resources, competency development, referrals and partners, data management, curriculum, and support systems. Employing a quantitative survey approach, this study involved distributing a questionnaire of 55 items covering the 14 aspects to 25 kindergarten schools across five sub-districts in Malang City. Findings reveal that only 12% of institutions possess a high capacity, while 88% fall into the medium category. Specific aspect evaluations showed: Regulations (89.30%), Management (72.60%), Funding (50.00%), Organization (47.60%), Socialization (47.60%), Physical Environment (47.60%), Facilities (45.30%), Services (35.65%), Human Resources (32.30%), Competency Development (31.70%), Referrals and Partners (28.50%), Data (24.40%), Curriculum (23.80%), and Support Systems (23.80%). Conclusively, inclusive Early Childhood Education in Malang City remains suboptimal. Implementation barriers include low awareness among community members, parents, and teachers regarding special needs contexts, limited facilities, insufficient competent educators, inadequate local governmental support, and budgetary constraints